Small informational size and interim cores of large quasilinear economies - Yusuke Kamishiro; Roberto Serrano (Brown University, Department of Economics, 2018)
We provide nonemptiness results of approximate interim cores with endogenous communication in large quasilinear economies, where every agent's informational size is small. We offer results for both replica and more general sequences of economies.
Keywords: C71; C72; D51; D82; 330; Asymmetric Information; Large Quasilinear Economies; Informational Smallness; Approximate Interim Cores